THE DEVELOPMENT OF MUSICAL SCIENCE IN THE MIDDLE AGES IN CENTRAL ASIA - Gofforov Ulmas Normatovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the history of the development of musical science in Central Asia in the Middle Ages.